2021
DOI: 10.3390/ani11082390
|View full text |Cite
|
Sign up to set email alerts
|

Blend of Essential Oils Supplemented Alone or Combined with Exogenous Amylase Compared with Virginiamycin Supplementation on Finishing Lambs: Performance, Dietary Energetics, Carcass Traits, and Nutrient Digestion

Abstract: Two experiments were conducted to compare a supplemental blend of essential oils alone (EO) or combined with enzymes (EO + ENZ) versus virginiamycin (VM), on characteristics of growth performance (Exp. 1) and digestion (Exp. 2) in finishing lambs. Lambs were fed a high-energy finishing diet supplemented with: (1) no supplement (control); (2) 150 mg supplemental EO; (3) 150 mg supplemental EO plus 560 mg alpha-amylase (EO + ENZ); and 4) 25 mg VM. Compared with the control, growth performance response to EO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…Except for the stomach complex and liver, in this study, supplementation of increasing doses of PA did not affect the weight of internal and external organs of finishing lambs. Similar results were previously reported by Orzuna-Orzuna et al [ 6 ] in lambs supplemented with increasing doses of PA (0, 1, 2, and 3 g kg −1 DM for 56 days) based on Acacia concinna , Balanites roxburghii, and Saccharum officinarum and by Estrada-Angulo et al [ 18 ] in lambs fed on high-concentrate diets and supplemented with 150 mg d −1 of essential oils (mixture of eugenol, thymol, limonene, and vanillin).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Except for the stomach complex and liver, in this study, supplementation of increasing doses of PA did not affect the weight of internal and external organs of finishing lambs. Similar results were previously reported by Orzuna-Orzuna et al [ 6 ] in lambs supplemented with increasing doses of PA (0, 1, 2, and 3 g kg −1 DM for 56 days) based on Acacia concinna , Balanites roxburghii, and Saccharum officinarum and by Estrada-Angulo et al [ 18 ] in lambs fed on high-concentrate diets and supplemented with 150 mg d −1 of essential oils (mixture of eugenol, thymol, limonene, and vanillin).…”
Section: Discussionsupporting
confidence: 91%
“…However, in cattle fed on a high-concentrate diet, Rivera-Méndez et al [ 24 ] observed that dietary supplementation of hydrolyzable tannins (6 g kg −1 DM for 84 days) increased ObsNEm and ObsNEg by 2 and 3%, respectively. Similarly, Estrada-Angulo et al [ 18 ] observed that, compared to CON, dietary supplementation with 150 mg d −1 of a mixture of essential oils (eugenol, thymol, vanillin, and limonene) increased ObsNEm and ObsNEg in lambs by 5 and 6%, respectively. Tannins, flavonoids, and essential oils were reported to reduce enteric methane production and increase ruminal propionate concentration in sheep and cattle [ 9 , 15 , 25 ], which would explain the positive effects of the PA used in the present study on ObsNEm and ObsNEg.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations